2011
DOI: 10.1136/jfprhc-2011-100119
|View full text |Cite
|
Sign up to set email alerts
|

Young men, sexual health and responsibility for contraception: a qualitative pilot study

Abstract: Background and methodology Despite increasing interest over the last decade or more in men's views of sexual health services and use of contraception, most published literature focuses on women. It is important that the views of boys and young men are better understood, particularly with regard to responsibility for use of contraception. This pilot study aimed to gain insights into young men's views of sexual health services and contraception; fi ve non-fathers aged between 14 and 18 years took part in two foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Despite low socioeconomic status being linked to risky sexual practices among young men, 28 32 there have been few in-depth studies focusing on contraceptive use amongst socially excluded young males. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Despite low socioeconomic status being linked to risky sexual practices among young men, 28 32 there have been few in-depth studies focusing on contraceptive use amongst socially excluded young males. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Although this did not result in any direct contact with potential participants it did raise the profile of the study and meant that, when approached, young men were potentially aware of the study. Difficulty recruiting young men for research of this type is not uncommon and has been reported (Brown, 2012). Local authority leisure centres were chosen as they are widely accessed in the South Wales valleys and options for accessing this group for research purposes have previously been discussed (Sydor, 2013).…”
Section: Methodsmentioning
confidence: 99%